Boletı́n de la Asociación Matemática Venezolana, Vol. XII, No. 1 (2005) 43 Some properties of solutions for the generalized thin film equation in one space dimension Changchun Liu Abstract In this paper, the author studies a generalized thin film equation in one space dimension. Some results on the finite speed of propagation of perturbations and regularity of solutions are established. 1 Introduction In this paper, we consider the variant version of the thin film equation, namely ∂u + div(|∇∆u|p−2 ∇∆u) = 0, ∂t x ∈ Ω, t > 0, p > 2, (1.1) where Ω ⊂ RN is a bounded domain with smooth boundary. The equation (1.1) is a typical higher order equations, which have a sharp physical background and a rich theoretical connotation. It was J.R.King [6] who first derived the equation. Equation (1.1) describes the surface tension driven evolution of the height u(x, t) of a thin liquid film on a solid surface in lubrication approximation [6, 7, 9]. The exponent p is related to the rheological properties of the liquid: p = 2 corresponds to a Newtonian liquid, whereas p 6= 2 emerges when considering “power-law” liquids. When p > 2 the liquid is said to be “shear-thinning”. J.R.King [6] studied Cauchy problem of the equation for one-dimensional, exploiting local analyses about the edge of the support and special closed form solutions such as travelling waves, separable solutions, instantaneous source solutions. On the basis of physical consideration, as usual the equation (1.1) is supplemented with the natural boundary value conditions u = ∆u = 0, x ∈ ∂Ω, t > 0. (1.2) The boundary value conditions (1.2) is a reasonable for the thin film equation or the Cahn-Hilliard equation, (see [1, 2, 4]) and initial value condition u(x, 0) = u0 (x), x ∈ Ω. (1.3) 44 C. Liu This equation is something quite like the p-Laplacian equation, but many methods used in the p-Laplacian equation such as those methods based on maximun principle are no longer valid for this equation. Because of the degeneracy, the problem (1.1)-(1.3) does not admit classical solutions in general. So, we introduce weak solutions in the following sense Definition A function u is said to be a weak solution of the problem (1.1)– (1.3), if the following conditions are satisfied: 1) u ∈ L∞ (0, T ; W 3,p (Ω)) ∩ C(0, T ; L2 (Ω)), u, ∆u ∈ W01,p (Ω), ∂u ∞ −1,p0 (Ω)), where p0 is the conjugate exponent of p; ∂t ∈ L (0, T ; W ∞ 2) For any ϕ ∈ C0 (QT ), the following integral equality holds: ZZ ZZ ∂ϕ dxdt + u |∇∆u|p−2 ∇∆u∇ϕ dxdt = 0; ∂t QT QT 3) u(x, 0) = u0 (x), in L2 (Ω) In [8] they prove the existence and uniqueness of weak solution for dimension N ≤ 2. This paper is a further step in the study of the properties of solutions, we proved the finite speed of propagation of perturbations and regularity of solutions of the problem (1.1)-(1.3) for one dimensional case. In addition, through out this paper, we set I = (0, 1). 2 Finite speed of propagation of perturbations In this section, we are going to prove the following theorem. Theorem 2.1 Assume p > 2, supp u0 ⊂ [x1 , x2 ], 0 < x1 < x2 < 1, and u is the weak solution of the problem (1.1)-(1.3), then for any fixed t > 0, we have supp u(x, ·) ⊂ [x1 (t), x2 (t)] ∩ [0, 1], 1 1 where x1 (t) = x1 − C1 t 3p−2 , x2 (t) = x2 + C2 t 3p−2 , p−2 ! 2(3p−2) Z T Z x1 Z 3 p C1 = C |D u| dxdτ , C2 = C 0 0 0 T Z p−2 ! 2(3p−2) 1 3 p |D u| dxdτ x2 C = 23p−2 (2p + 1)p (p − 1)p−1 (1 + p−p ). To prove the Theorem 2.1 we need the following result Lemma 2.2 The weak solution u of the problem (1.1)-(1.3), satisfying for any 0 ≤ ρ ∈ C 2 (I), Z Z 1 1 1 1 ρ(x)|Du(x, t)|2 dx − ρ(x)|Du0 (x)|2 dx 2 0 2 0 ZZ = − |D3 u|p−2 D3 uD2 (ρ(x)Du) dx, Qt , Properties of solutions for thin film equation where Qt = (0, 1) × (0, t), D = 45 ∂ ∂x . Proof. Similar to the discussion in [8], we can also easily prove that for any 0 ≤ ρ ∈ C 2 (Ω), Z 1 ρ(x)|Du(x, t)|2 dx ∈ C([0, T ]). fρ (t) = 2 Ω Consider the functional 1 Φρ [v] = 2 Z ρ(x)|Dv(x)|2 dx. Ω It is easy to see that Φρ [v] is a convex functional on H01 (Ω). For any τ ∈ (0, T ) and h > 0, we have Φρ [u(τ + h)] − Φρ [u(τ )] ≥ hu(τ + h) − u(τ ), −D(ρ(x)Du(τ ))i. δΦ [v] ρ = −D(ρ(x)Dv), for any fixed t1 , t2 ∈ [0, T ], t1 < t2 , integrating the By δv above inequality with respect to τ over (t1 , t2 ) , we have Z t2 +h Z t1 +h Z t2 hu(τ +h)−u(τ ), −D(ρ(x)Du(τ ))i dτ. Φρ [u(τ )] dτ − Φρ [u(τ )] dτ ≥ t2 t1 t1 Multiplying both sides of the above equality by h1 , and letting h → 0, we obtain Z t2 ∂u Φρ [u(t2 )] − Φρ [u(t1 )] ≥ h , −D(ρ(x)Du(τ ))i dτ. ∂t t1 Similarly, we have Φρ [u(τ )] − Φρ [u(τ − h)] ≤ h(u(τ ) − u(τ − h)), −D(ρ(x)Du(τ ))i. Thus Z t2 Φρ [u(t2 )] − Φρ [u(t1 )] ≤ h ∂u , −D(ρ(x)Du(τ ))i dτ, ∂t h ∂u , −D(ρ(x)Du(τ ))i dτ. ∂t t1 and hence Z t2 Φρ [u(t2 )] − Φρ [u(t1 )] = t1 Taking t1 = 0, t2 = t, we get from the definition of solutions that Z t Φρ [u(t)] − Φρ [u(0)] = h−D(|D3 u|p−2 D3 u), −D(ρ(x)Du(τ ))i dτ 0 Z t h|D3 u|p−2 D3 u, D2 (ρ(x)Du(τ ))i dτ. = − 0 46 C. Liu This completes the proof. Proof of Theorem 2.1 By Lemma 2.2, take ρ(x) = (x − y)s+ , y ∈ [x2 , 1), we have Z Z tZ 1 1 1 |D3 u|p−2 D3 uD2 [(x − y)s+ Du)] dxdτ. (x − y)s+ |Du(x, t)|2 dx = − 2 0 0 0 Denote the left side of above equality by J, then we have Z tZ 1 |D3 u|p−2 D3 uD2 [(x − y)s+ Du] dxdτ J = − 0 0 Z tZ 1 (x − y)s+ |D3 u|p dxdτ = − 0 tZ 1 0 Z −2s 2 3 p−2 3 (x − y)s−1 D u dxdτ + D u|D u| 0 0 1 Z tZ s−2 (x − y)+ |D3 u|p−2 D3 uDu dxdτ −s(s − 1) 0 Z tZ ≤ (x − y)s+ |D3 u|p dxdτ + − 0 0 Z tZ (x − 0 1 + 4 Z tZ 1 2 Z tZ − Z tZ s−p y)+ |D2 u|p 0 y)s+ |D3 u|p 0 0 (x − y)s+ |D3 u|p dxdτ + C1 0 s−2p (x − y)+ |Du|p dxdτ 0 Z tZ 0 Z tZ 1 dxdτ + C2 1 1 s−p (x − y)+ |D2 u|p dxdτ 0 1 s−2p (x − y)+ |Du|p dxdτ, +C2 0 (x − y)s+ |D3 u|p dxdτ Z tZ 0 0 1 dxdτ 0 1 (x − 0 1 4 1 +C1 ≤ 0 1 0 using Hardy inequality [5], we have Z 1 Z 1 s−p p |D2 u|p dx. |Du| dx ≤ C (x − y)+ (x − y)s−2p + 0 0 Hence Z 1 2 1 y)s+ |Du|p 1 dx + 2 Z tZ 1 (x − (x − y)s+ |D3 u|p dxdτ 0 0 0 Z tZ 1 2 p ≤ C1 (x − y)s−p + |D u| dxdτ. 0 (2.1) 0 Thus Z (x − sup 0<τ ≤t 1 0 y)s+ |Du|p Z tZ dx ≤ C1 0 0 1 s−p (x − y)+ |D2 u|p dxdτ, (2.2) 47 Properties of solutions for thin film equation and 1 Z tZ 1 Z tZ s−p (x − y)+ |D2 u|p dxdτ. (2.3) For (2.2) again using Hardy inequality, we have Z tZ 1 Z 1 s p (x − y)s+ |D3 u|p dxdτ. sup (x − y)+ |Du| dx ≤ C (2.4) y)s+ |D3 u|p (x − dxdτ ≤ C1 0 0 0 0 0<τ ≤t 0 0 0 Let Z tZ Es (y) = Z tZ 1 (x − y)s+ |D3 u|p dxdτ, E0 (y) = |D3 u|p dxdτ. y 0 0 0 1 In (2.3), set s = 2p + 1 and using Nirenberg inequality [3], we have E2p+1 (y) ZZ 2 p ≤ C1 (x − y)p+1 + |D u| dxdτ Qt Z t Z 1 ≤ C (x − 0 where 1 p = 3 p y)p+1 + |D u| a Z (1−a)p/2 p+1 2 dx (x − y)+ |Du| dx dτ, 0 1 p+2 Ω a( p1 + − 2 p+2 ) + (1 − 0<a= a) 21 , 1 p 1 p − − therefore 1 p+2 2 p+2 − − 1 2 1 2 < 1. Using (2.4) we obtain E2p+1 (y) ZZ (1−a)p/2 Z t Z 1 3 p 3 p a ≤ C (z − z0 )p+1 |D u| dxdτ ((x − y)p+1 + + |D u| dx) dτ Qt 0 (1−a)p/2 ZZ ≤ C[Ep+1 (y)] (x − 3 p y)p+1 + |D u| 0 a dxdτ t1−a Qt ≤ CEp+1 (y)(1−a)p/2+a t1−a . Denote λ = 1 − a, γ = a + (1 − a)p/2. Applying Hölder’s inequality, we have E2p+1 (y) ZZ γ p+1 λ 3 p ≤ Ct (x − y)+ |D u| dxdτ Qt ≤ Ct λ ZZ (x − y)2p+1 |D3 u|p + (p+1)γ Z t Z (2p+1) ≤ Ctλ [E2p+1 (y)](p+1)γ/(2p+1) [E0 (y)]pγ/(2p+1) . 3 p |D u| dxdτ dxdτ Qt 1 0 y pγ (2p+1) 48 C. Liu Therefore E2p+1 (y) ≤ Ctλ/σ [E0 (y)]pγ/((2p+1)σ) , σ =1− p+1 γ > 0. 2p + 1 Using Hölder’s inequality again, we get E1 (y) ≤ [E2p+1 (y)]1/(2p+1) [E0 (y)]2p/(2p+1) ≤ Ctγ1 [E0 (y)]1+θ , where γ1 = λ , σ(2p + 1) θ= 1 pγ − > 0. 2 σ(2p + 1) 2p + 1 Noticing that E10 (y) = −E0 (y), we obtain E10 (y) ≤ −Ct−γ1 /(θ+1) [E1 (y)]1/(θ+1) . If E1 (x2 ) = 0, then suppu ⊂ [0, x2 ]. If E1 (x2 ) > 0, then there exists a maximal interval (x2 , x∗2 ) in which E1 (y) > 0, E1 (x∗2 ) = 0 and h E1 (y)θ/(θ+1) i0 = E10 (y) θ ≤ −Ct−γ1 /(θ+1) . θ + 1 [E1 (y)]1/(θ+1) Integrating the above inequality over (x2 , x∗2 ), we have E1 (x∗2 )θ/(θ+1) − E1 (x2 )θ/(θ+1) ≤ −Ct−γ1 /(θ+1) (x∗2 − x2 ), which implies that x∗2 ≤ x2 + Ctµ (E0 (x2 ))θ/(θ+1) ≡ x2 (t), µ= 1 γ1 = > 0. θ+1 3p − 2 Results in [8] imply that E0 (y) can be controlled by a constant C independent of y. Therefore suppu(·, t) ⊂ [0, x2 (t)]. Similarly, we have suppu(·, t) ⊂ [x1 (t), 1]. We have thus completed the proof of Theorem 2.1. 3 Regularity of solutions Theorem 3.1 If u is weak solution of the problem(1.1)-(1.3), then for any (x1 , t1 ), (x2 , t2 ) ∈ QT , we have |u(x1 , t1 ) − u(x2 , t2 )| ≤ C(|x1 − x2 | + |t1 − t2 |1/2 ), where C is a constant depending only on p. 49 Properties of solutions for thin film equation Proof. Let Z T Z jε (x − y, t − s)u(y, s) dyds uε (x, t) = Jε u(x, t) = 0 |x−y|<ε where jε (x, t) is a mollifier. For any x1 , x2 ∈ I, we have uε (x1 , t) − uε (x2 , t) Z TZ Z = jε (x1 − y, t − s)u(y, s)dyds − 0 R T Z jε (x2 − y, t − s)u(y, s) dyds R ∂jε (zx1 + (1 − z)x2 − y, t − s) u(y, s) dzdyds ∂z R Z Z 1 Dx jε (zx1 + (1 − z)x2 − y, t − s)(x1 − x2 )u(y, s) dzdyds 0 T = 0 R 0 T Z Z 1 Z = − Dy jε (zx1 + (1 − z)x2 − y, t − s)(x1 − x2 )u(y, s) dzdyds 0 T Z Z Z = Z 0 T R Z Z 0 1 jε (zx1 + (1 − z)x2 − y, t − s)Dy u(y, s) dzdyds(x1 − x2 ). = 0 R 0 Therefore |uε (x1 , t) − uε (x2 , t)| Z T Z Z ≤ 1 |jε (zx1 + (1 − z)x2 − y, t − s)||Dy u(y, s)| dzdyds|x1 − x2 |, 0 R 0 by u ∈ L∞ (0, T ; W 3,p (Ω)), hence using Sobolev embedding theorem, we have ∂u ∞ ∞ ∂x ∈ L (QT ) and u ∈ L (QT ). Thus we obtain |uε (x1 , t) − uε (x2 , t)| ≤ C|x1 − x2 |. (3.1) Set 0 < ε < t1 < t2 < T . Let ∆t = t2 −t1 , Iρ = I(∆t)1/2 (x0 )= (x0 −(∆t)1/2 , x0 + (∆t)1/2 ), x0 ∈ I, choose ρ sufficiently small, such that Iρ ⊂ I, ϕ ∈ C01 (Iρ ), we 50 C. Liu can obtain Z ϕ(x)(uε (x, t2 ) − uε (x, t1 )) dx Z 1 ∂uε (x, st2 + (1 − s)t1 ) dsdx ϕ(x) ∂s Iρ 0 Z Z 1Z T Z ∆t u(y, τ )· ϕ(x) ZIρ = = Iρ (3.2) |x−y|<ε 0 0 ·j (x − y, st2 + (1 − s)t1 − τ ) dydτ dsdx Z εt 1Z T Z u(y, τ )· ϕ(x) Z = −∆t Iρ |x−y|<ε 0 0 ·jετ (x − y, st2 + (1 − s)t1 − τ ) dydτ dsdx. Fixed (x, t) ∈ QT , 0 < ε < t < T − ε, we have jε (x − y, t − τ ) ∈ C01 (QT ), from definition of weak solution Z TZ jετ (x − y, st2 + (1 − s)t1 − τ )u(y, τ ) dydτ |x−y|<ε 0 Z T Z |Dy3 u|p−2 Dy3 uDy jε (x − y, st2 + (1 − s)t1 − τ )u(y, τ ) dydτ, = − 0 |x−y|<ε hence (3.2) is converted into Z ϕ(x)(uε (x, t2 ) − uε (x, t1 )) dx Iρ Z Z = Z T Z |Dy3 u|p−2 Dy3 u · ϕ(x) ∆t Iρ Z = 1 ∆t 0 1 0 Z |x−y|<ε 0 ·Dy jε (x − y, st2 + (1 − s)t1 − τ )u(y, τ ) dydτ dsdx Z TZ Dx ϕ(x) |Dy3 u|p−2 Dy3 u · Iρ |x−y|<ε 0 ·jε (x − y, st2 + (1 − s)t1 − τ )u(y, τ ) dydτ dxds. Taking Z (∆t)1/2 −|x−x0 |−2h ϕ(x) = ϕh (x) = δh (s) ds, −h R where δ(s) ∈ C01 (R); δ(s) ≥ 0; δ(s) = 0, as |s| ≥ 1; R δ(s) ds = 1. For h > 0 define δh (s) = h1 δ( hs ). Hence Z ϕh (x)(uε (x, t2 ) − uε (x, t1 )) dx Iρ Properties of solutions for thin film equation Z = 1 Z ∆t 0 δh ((∆t)1/2 − |x − x0 | − 2h) Iρ 51 x0 − x Jε (|D3 u|p−2 D3 u) dxds, |x − x0 | Noting that for x ∈ Iρ , lim ϕh (x) = 1, and if |x − x0 | < (∆t)1/2 − h, then h→0 δh ((∆t)1/2 − |x − x0 | − 2h) = 0. δh ≤ C h, and m(Iρ \I(∆t)1/2 −|x−x0 |−2h ) ≤ Ch. By Jε (|D3 u|p−2 D3 u) ≤ C, therefore Z ϕh (x)(uε (x, t2 ) − uε (x, t1 )) dx ≤ C∆t. Iρ Letting h → 0, we obtain Z (uε (x, t2 ) − uε (x, t1 )) dx ≤ C∆t. Iρ Applying the mean value theorem, we see that for some x∗ ∈ Iρ such that |uε (x∗ , t2 ) − uε (x∗ , t1 )| ≤ C(∆t)1/2 . Taking this into account and using (3.1), it follows that |uε (x, t2 ) − uε (x, t1 )| ≤ |uε (x, t2 ) − uε (x∗ , t2 )| + |uε (x∗ , t2 ) − uε (x∗ , t1 )| + |uε (x∗ , t1 ) − uε (x, t1 )| ≤ C(∆t)1/2 , letting ε → 0, we known that u is Hölder continuous. This completes the proof. References [1] F. Bai, C. M. Elliott, A. Gardiner, A. Spence & A.M.Stuart, The viscous Cahn-Hilliard equation, part I: computations, Nonlinearity, 8(1995), 131160. [2] E. Beretta, M. Bertsch and R. Dal Passo, Nonnegative solutions of a fourth order nonlinear degenerate parabolic equation, Arch. Rational Mech. Anal., 129(2)(1995), 175-200. [3] F. Bernis, Qualitative properties for some nonlinear higher order degenerate parabolic equations, Houston J. Math. 14(3)(1988), 319-352. 52 C. Liu [4] C. M. Elliott and A. M. Stuart, The viscous Cahn-Hilliard equation. Part II Analysis, J. Diff. Equations, 128(1996), 387–414. [5] G. H. Hardy, J. E. Littlewood and G. P’olya, Inequalities, Cambridge University press, Cambridge, 1952. [6] J. R. King, Two generalisations of the thin film equation, Math. Comput. Modelling, 34(7-8)(2001), 737-756. [7] J. R. King, Thin film flows and higher order degenerate parabolic equations, IUTAM Symposium on Free Surface Flows, A. C. King & Y. D. Shikhmurzaev (eds), Kluwer Academic Publishers, 2001, 7-18. [8] Liu Changchun, Yin Jingxue and Gao Hongjun, A generalized thin film equation, Chin. Ann. Math., 25B(3)(2004), 347-358. [9] A. Oron, S. H. Davis and G. Bankoff, Long scale evolution of thin liquid films, Rev. Mod. Phys. 69(1997), 931-980. Changchun Liu Department of Mathematics, Jilin University, Changchun 130012, China lcc@email.jlu.edu.cn